Auditoria en seguridad vial vía Armenia-Pereira, Km 0+000 al Km 9+000 (2024)
In this project, a road safety audit was carried out in the municipality of Armenia located in the section between the abscissa km 0+000 to km 9+000 of the Armenia-Pereira highway. To carry out this audit, a descriptive and quantitative methodology was used in order to identify and describe the possible risks observed during the road inspection.